Al-Qiymah al-Akhlaqiyah fi al-Qishhati al-Qasirah "Al-Hadiqah an-Nazdhifah - khasanah, Mushokhikhul; Utami, Shinta Fitria; Muttaki, Muttaki (Al-Manar, 2025)
AbstractThe advancement of technology has made it easier for people to access the internet without limitations. While the internet offers numerous benefits to human life, it also has negative aspects. One of the concerning issues is the moral decline of children frequently exposed to online content. Literature, as a direct reflection of human experience, plays a crucial role as a moral guide, particularly for children, through fables.This study aims to explore the moral values embedded in the children's short story al-Ḥadīqah al-Naẓīfah by employing Thomas Lickona’s moral theory. The research adopts a library-based approach with a descriptive-analytical method. The data consists of words, phrases, and sentences found in the short story. Data collection was carried out through careful reading, translation for deeper understanding, and note-taking.The data analysis begins with an examination of the intrinsic elements of al-Ḥadīqah al-Naẓīfah, which are then correlated with Thomas Lickona’s moral theory. The findings reveal that the short story al-Ḥadīqah al-Naẓīfah conveys moral values related to environmental cleanliness awareness.Keywords: short stories; children's literature; moral values